Peningkatkan Kemampuan Konsep Angka Anak Melalui Kegiatan Roda Putar di TK Islam Silaturahmi Kabupaten Padang Pariaman - Sarmiati, Mimi; Wirman, Asdi (Penerbit Aksara Rentaka Siar (ARS), 2020)
The introduction of the concept of numbers given to children aims so that a child can better understand the concept of these numbers and can apply the surrounding environment or in everyday life so that aspects of child development develop well. This study aims to improve the ability of the concept of children's numbers through the activities of the turning wheel in Group B Islamic Kindergarten in Padang Pariaman. This type of research is a classroom action research (Classroom Action). Data collection techniques are through observation while the analysis technique used is the percentage. The results of research in primagama padang creative kindergartens that the reading ability of children increased from each meeting can be seen from the average in the first cycle 42.67% increased in the second cycle to 80% with the activity of the turning wheel in the ability of the child number concept.